The Effect of Metformin Consumption on Mortality in Hospitalized COVID-19 patients: a systematic review and meta-analysis - Lukito, Antonia Anna (Diabetes Metab Syndr, 2020)
BACKGROUND AND AIMS: Diabetes is one of the most common comorbidities, and it is associated with poorer outcomes in patients with coronavirus disease 2019 (COVID-19). Preliminary findings showed that mortality was reduced in those who consume metformin compared to those who did not, and given its low cost and widespread availability; metformin is an attractive and potential agent to mitigate excessive risk in diabetic populations. METHODS: Several medical databases (Pubmed, EuropePMC, EBSCOhost, Proquest, Cochrane library) and two health-science preprint servers (preprint.org and Medrxiv) were systematically searched for relevant literature. RESULTS: Nine studies with 10,233 subjects were included in the qualitative and quantitative synthesis. Meta-analysis showed that metformin is associated with lower mortality in pooled non-adjusted model (OR 0.45 [0.25, 0.81], p = 0.008; I(2:) 63.9%, p = 0.026) and pooled adjusted model (OR 0.64 [0.43, 0.97], p = 0.035; I(2): 52.1%, p = 0.064). CONCLUSION: The analysis showed that metformin consumption was associated with lower mortality. Randomized controlled trials are needed to confirm this finding.